(3GdeUfas - (3CHh HcQ YHO GdQRGb Hf geGe Hf fGaY GdMejQj GdUfYGfj Gdjefj, GdUfYGfj,J (B211 (3g` s
(3ChdgG (B:s
(3jHJOF HHGH (B: (3GdQLd jWdb KdGKoG eaJQbI ef cJGH GdWdGb s
(3BNQgG (B:s
(3hjfJgi HHGH (B: (3ef eGJ hYdjg Ojf (B" (3ef cJGH GdHjhY s
(3ef GdfSNI faSgGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B353s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B105 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1712s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs